IMPLEMENTATION OF THE PROBLEM-POSING LEARNING METHOD TO INCREASE STUDENT’S ACTIVE PARTICIPATION IN MATHEMATICS - Etik Rohmatika Etik Rohmatika (Journal Of Resource Management, Economics And Business, 2023)
Purpose: This study aims to analyse the impact of the implementation of Problem-Posing Learning method to the student’s active participation and study results in Mathematics subject. Research Methodology: This study uses Classroom Action Research and Paired t-test by using the pre-test and post-test score. Results: The application of problem-posing learning method can increase students’ active participation and grade in Mathematics subject. Limitations: This study analyses the impact of Problem-Posing Learning method in Mathematics subject. Contribution: The results contribute to the education field in terms of effective learning model to increase students’ active participation and study results.